Bedding-generated particulate matter: implications for rodent studies. (24th August 2019) - Hudda, Neelakshi; Durant, John L.; Nemeth, Alexandra; Mann, Phyllis; Petitto, Jocelyn; Brugge, Douglas; Nephew, Benjamin C.
Abstract: Objectives: Rodents used in scientific research are typically housed in cages containing natural bedding materials. Despite extensive evidence of biological harm from inhaled particulate matter (PM), relatively little work has been performed to measure bedding-generated PM exposure in caged animals used in basic science research. Our objectives were to determine whether bedding-generated PM was present in significant concentrations in rodent cages and to identify the main factors affecting the accumulation and attenuation of bedding-generated PM inside cages. Materials and Methods: We measured PM2.5 concentrations in cages containing common bedding materials (pine, aspen, paper, and corncob) with filter top isolator absent or present on the cages. PM2.5 concentrations were monitored with rats inside cages as well as during artificial manipulation of the bedding (designed to simulate rodent activity). Results and Discussion: Upon rodent digging or mechanical/manual stirring, all four bedding materials produced significant increases in PM2.5 concentrations (as much as 100–200 µg/m3 PM2.5, 50- to 100-fold higher than during periods of no rodent activity), and concentrations in cages fitted with filter tops were an order of magnitude higher than in cages without filter tops. Elevated concentrations were sustained for longer durations in cages with filter tops (5–10 minutes) compared to cages with only bar lids (0–2 minutes). Conclusions: These results indicate that standard laboratory housing conditions can expose rodents to substantial levels of PM2.5. Bedding-generated PM has potential implications as an environmental agent in rodent studies.